Stroke : the comprehensive and medically accurate manual about stroke and how to deal with it - Rudd, Anthony (At your fingertips (London, England), 2005)
In the new, second edition of this inspiring guide, three leading experts answer hundreds of questions actually asked by people who have experienced stroke and their families. Stroke - the 'at your fingertips' guide gives you up-to-date and medically accurate information on a range of topics covering "what is stroke" to "future developments